A case of recurrent epilepsy‐associated rosette‐forming glioneuronal tumor with anaplastic transformation in the absence of therapy. Issue 5 (21st August 2019) - Halfpenny, Aaron; Ferris, Sean P.; Grafe, Marjorie; Woltjer, Randy; Selden, Nathan; Nazemi, Kellie; Perry, Arie; Solomon, David A.; Gultekin, Sakir H.; Moore, Stephen; Olson, Susan; Lawce, Helen; et al.
Abstract : Rosette‐forming glioneuronal tumor (RGNT) most commonly occurs adjacent to the fourth ventricle and therefore rarely presents with epilepsy. Recent reports describe RGNT occurrence in other anatomical locations with considerable morphologic and genetic overlap with the epilepsy‐associated dysembryoplastic neuroepithelial tumor (DNET). Examples of RGNT or DNET with anaplastic change are rare, and typically occur in the setting of radiation treatment. We present the case of a 5‐year‐old girl with seizures, who underwent near total resection of a cystic temporal lobe lesion. Pathology showed morphologic and immunohistochemical features of RGNT, albeit with focally overlapping DNET‐like patterns. Resections of residual or recurrent tumor were performed 1 year and 5 years after the initial resection, but no adjuvant radiation or chemotherapy was given. Ten years after the initial resection, surveillance imaging identified new and enhancing nodules, leading to another gross total resection. This specimen showed areas similar to the original tumor, but also high‐grade foci with oligodendroglial morphology, increased cellularity, palisading necrosis, microvascular proliferation, and up to 13 mitotic figures per 10 high power fields. Ancillary studies the status by sequencing showed wild‐type of the isocitrate dehydrogenase 1 (IDH1), IDH2, and human histone 3.3 (H3F3A) genes, and BRAF studies were negative for mutation or rearrangement. Fluorescence in situ hybridization (FISH) showed codeletion of 1p and 19q limited to the high‐grade regions. By immunohistochemistry there was loss of nuclear alpha‐thalassemia mental retardation syndrome, X‐linked (ATRX) expression only in the high‐grade region. Next‐generation sequencing showed an fibroblast growth factor receptor receptor 1 (FGFR1) kinase domain internal tandem duplication in three resection specimens. ATRX mutation in the high‐grade tumor was confirmed by sequencing which showed a frameshift mutation (p.R1427fs), while the apparent 1p/19q‐codeletion by FISH was due to loss of chromosome arm 1p and only partial loss of 19q. Exceptional features of this case include the temporal lobe location, 1p/19q loss by FISH without true whole‐arm codeletion, and anaplastic transformation associated with ATRX mutation without radiation or chemotherapy.